Low chikungunya virus seroprevalence two years after emergence in Fiji. (January 2020) - Aubry, Maite; Kama, Mike; Henderson, Alasdair D.; Teissier, Anita; Vanhomwegen, Jessica; Mariteragi-Helle, Teheipuaura; Paoaafaite, Tuterarii; Manuguerra, Jean-Claude; Christi, Ketan; Watson, Conall H.; Lau, Colleen L.; Kucharski, Adam J.; et al.
Highlights: Chikungunya virus (CHIKV) infections were recorded in Fiji between 2015 and 2017. We performed serological testing on serum from 320 Fijians sampled in 2017. CHIKV seroprevalence increased from 0.9% in 2015 to 12.8% in 2017. Of the 198 participants seronegative in 2015, 31 (15.7%) were seropositive in 2017. Low CHIKV transmission occurred during the two years following emergence in Fiji. Abstract: Objectives: In Fiji, autochthonous chikungunya virus (CHIKV) infection was first detected in March 2015. In a previous serosurvey conducted during October–November 2015, we reported a prevalence of anti-CHIKV IgG antibodies of 0.9%. In the present study, we investigated the seroprevalence of CHIKV two years after its emergence in Fiji. Methods: Sera from 320 residents of Fiji recruited in June 2017, from the same cohort of individuals that participated in the serosurvey in 2015, were tested for the presence of IgG antibodies against CHIKV using a recombinant antigen-based microsphere immunoassay. Results: Between 2015 and 2017, CHIKV seroprevalence among residents increased from 0.9% (3/333) to 12.8% (41/320). Of the participants with available serum samples collected in both 2015 and 2017 (n = 200), 31 (15.5%) who were seronegative in 2015 had seroconverted to CHIKV in 2017. Conclusions: Our findings suggest that low-level transmission of CHIKV occurred during the two years following the emergence of the virus in Fiji. No CHIKV infection has been reported in Fiji since 2017, but due to the presumed low herd immunity of the population, the risk of CHIKV re-emergence is high. Consequently, chikungunya should be considered in the differential diagnosis of acute febrile diseases in Fiji.